Edukasi Perilaku Hidup Bersih dan Sehat (PHBS) di Kelompok Masyarakat Kebumen Gemilang Sejahtera Palembang - Nawawi, Rizki Andini; Amalia, Ella; Rivani, Erizka; Usman, Doni; Zanaria, Rima; Saputra, Firdaus Rizky; Adzanarasta, Achmad Riezky; Natasya, Cindy; Yosita, Dilla; Humaira, Nabila Tsabitah (Abdimas Universal, 2026)
Infectious disease remains a common risk in Indonesian societies. Clean and Healthy Lifestyle (CHL) is an effort to increase community health status in various settings. Communities involved in waste management are more at risk of contracting infectious diseases. Kebumen Gemilang Sejahtera (KGS) Community is a community movement in Palembang concerned with environmental issues, which manages household waste through its community waste bank. This community service activity aimed to increase the KGS Community members’ knowledge and awareness about infectious diseases through household CHL implementation. The activity was a direct visitation and in-person health education. The activity was carried out at KGS Waste Bank, situated at Jalan Sersan Zaini No. 2819, RT. 27, Dua Ilir Village, Ilir Timur II District, Palembang. Health education was carried out with supporting interactive multimedia presentation and poster, comprising of infectious disease risks, chain of infection, symptoms of infectious diseases, and indicators of household CHL, accompanied by relevant demonstrations from the team. There was an increase in household CHL knowledge among KGS Community members, which was shown by increased average posttest score compared to pretest score.